Secondary School Students Attitude Towards physical and sports activities And Its Relation To The Athletic Achievement Motives - arfis zoubir,; ou, (sports creativity, 2025)
This study aims to Determine the relationship between the attitudes governing the physical activity of secondary school students and the motivation of athletic achievement. Research Methodology : descriptive approach.Study and Sample population : 663 secondary school students from the province of M’sila (Algeria). Sample method : simple random sampling (SRS) method. Study Tools : The Kenyon Attitude Toward Physical Activity Scale, The Joe Willis Achievement Motive Scale. Results: There is a positive statistically significant relationship between the dimensions of attitudes towards physical activity (such as; social experience, health and fitness, tension and risk, aesthetic experience, stress reduction, athletic excellence) and the athletic achievement motivation among secondary school students, There is a positive statistically significant relationship between the attitudes of secondary school students towards physical and sports activities and the motives of athletic achievement.